2022
DOI: 10.1136/bmjdrc-2022-002910
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum creatinine to cystatin C ratio and subclinical atherosclerosis in patients with type 2 diabetes

Abstract: IntroductionSarcopenia index (SI), calculated by (serum creatinine/cystatin C)×100, is reported to be associated with sarcopenia. Few studies reported the association between SI and subclinical atherosclerosis. We evaluated the association between SI and subclinical atherosclerosis, assessed by brachial-ankle pulse wave velocity (baPWV).Research design and methodsOne hundred seventy-four patients with type 2 diabetes were included in this cross-sectional study. The relationship between SI and baPWV was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
6
1
1
Order By: Relevance
“…In this study, the percentage of SCAS in the T2DM population was 38.46%, lower than the 43.68% reported by Hashimoto et al in a Japanese T2DM population (22), which might be related to the region and sample size. Multiple studies have demonstrated an association between the TyG index and the incidence of CVD, coronary artery stenosis, stroke, and AS (23,24).…”
Section: Discussioncontrasting
confidence: 85%
“…In this study, the percentage of SCAS in the T2DM population was 38.46%, lower than the 43.68% reported by Hashimoto et al in a Japanese T2DM population (22), which might be related to the region and sample size. Multiple studies have demonstrated an association between the TyG index and the incidence of CVD, coronary artery stenosis, stroke, and AS (23,24).…”
Section: Discussioncontrasting
confidence: 85%
“…However, the complexity of sarcopenia assessment likely makes the formal screening for sarcopenia highly underutilized. The SI is a readily available biomarker of skeletal muscle mass that has been validated in several populations including critically ill 6 , older adults 32 , lung and kidney transplant recipients 7 , diabetic 33 and cancer patients 34 . Moreover, SI was found to be a prognostic factor for short- and long-term survival and complications among cancer patients 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine is generated in proportion to muscle mass; however, cystatin C levels are not affected by it [ 23 ]. Therefore, the serum creatinine to cystatin C ratio can be used to evaluate muscle mass in several diseases [ 24 - 26 ]. Similar to the results of the previous study, this study also showed a significant correlation between the serum creatinine to cystatin C ratio and muscle mass in patients with COPD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%